Effect of Seed Rates on the Production Components of some Barley Varieties (Latakia University Journal -Biological Sciences Series, 2018)
This research was carried out during the agricultural season 2014-2015 in the village of Asayba ,Banias region in Tartous province. According to the design of the complete random sectors, three replicates and the objective of the study the effect of seed rates on the productivity of barley varieties: improved white Arabic, Furat-2. In the study, four agricultural distances (1- 1.5-2 cm) were used for barley cultivars that are compatible with seed rates of 160-110-80-115 kg / h, respectively. The results of the study showed that the seed yield was 160 kg / h, which was significantly higher in yield and number of grains / spike than the rest of the seeds. In both cultivars, the yield was higher than 1000 g / 1000 tablets and the number of non-fruitful activities / m 2. The interaction was significant "between the white Arab variety and seed rate 160 kg / e, where it gave the highest productivity in the yield of biological and granular. Keywords: seed rates - barley – yield.